Investigating the current status of the student evaluation system in Iran University of Medical Sciences: A step to improve education - Shahnam Sedigh Maroufi; Parisa Moradimajd; Maryam Jalali; Ghobad Ramezani; Somayeh Alizadeh (Journal of Education and Health Promotion, 2021)
BACKGROUND: Medical education has special features due to the need various areas of learning. The present study was conducted to provide a complete picture of the evaluation system in Iran University of Medical Sciences for improving the evaluation system and medical sciences examinations. MATERIALS AND METHODS: The research was cross-sectional study that conducted through self-reporting of educational departments, a comprehensive review of the student evaluation system in the affiliated faculties of Iran University of Medical Sciences from 2017 to 2018. Educational members and heads of nine faculties and 80 departments participated in this study. The research tool was a researcher-made questionnaire, include two parts: (1) 10 general questions about the activities of the educational groups regarding the student evaluation system and (2) 20 questions about the types and quality of examinations. RESULTS: From 80 questionnaires, 71 were completed by the managers of the departments. The results showed that 62% of the faculty members in the educational departments in the last 2 years did not participate in the workshop on the methods of evaluation and making tests. 56% of the faculties have a reference for continuous monitoring of students' assessment and evaluation, and in 87% of the cases, the content is given in accordance with the objectives. The use of logbooks was more common (28%) than other methods to assess practical skills. CONCLUSION: Empower faculty members on the use of various tools, strengthening the supervision of formative evaluation and use of medical education graduates to promote evaluation methods seems necessary.